Age of First Exposure to American Football and Behavioral, Cognitive, Psychological, and Physical Outcomes in High School and Collegiate Football Players. (July 2019) - Brett, Benjamin L.; Huber, Daniel L.; Wild, Alexa; Nelson, Lindsay D.; McCrea, Michael A.
Background: Although some studies have observed a relationship between age of first exposure (AFE) to American football and long-term outcomes, recent findings in collegiate athletes did not observe a relationship between AFE and more intermediate outcomes at early adulthood. This, however, requires independent replication. Hypothesis: There will be no association between AFE to football and behavioral, cognitive, emotional/psychological, and physical functioning in high school and collegiate athletes. Study Design: Cross-sectional study. Level of Evidence: Level 3. Methods: Active high school and collegiate football players (N = 1802) underwent a comprehensive preseason evaluation on several clinical outcome measures. Demographic and health variables that significantly differed across AFE groups were identified as potential covariates. General linear models (GLMs) with AFE as the independent variable were performed for each clinical outcome variable. Similar GLMs that included identified covariates, with AFE as the predictor, were subsequently performed for each clinical outcome variable. Results: After controlling for covariates of age, concussion history, race, and a diagnosis of ADHD, earlier AFE (<12 vs ≥12 years) did not significantly predict poorer performance on any clinical outcome measures (all P > 0.05). A single statistically significant association between AFE group and somatization score was recorded, with AFE <12 years exhibiting lower levels of somatization. Conclusion: In a large cohort of active high school and collegiate football student-athletes, AFE before the age of 12 years was not associated with worse behavioral, cognitive, psychological, and physical (oculomotor functioning and postural stability) outcomes. Clinical Relevance: The current findings suggest that timing of onset of football exposure does not result in poorer functioning in adolescence and young adults and may contribute to resilience through decreased levels of physically related psychological distress.